Demographic, clinical, chest X-ray characteristics, and outcome of children admitted with acute bronchiolitis in the tertiary care hospital South India - Buddharaju, Chandradeve Varma B S K (Indian Journal of Child Health, 2022)
Aim and Objectives: The goal of this research was to assess the demographic, clinical, and radiological characteristics of children brought to the hospital with acute bronchiolitis. Materials and Methods: This is a prospective study of children aged 1–3 years whowere admitted to a tertiary care center with acute bronchiolitis between June and August 2021. The research excludes infants